2017
DOI: 10.1051/epjconf/201714902011
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of wakefields by relativistic electron bunches in the dielectric waveguide filled with radially inhomogeneous plasma

Abstract: One of shortcomings of the dielectric wakefield accelerators (DWA) limiting the effective length of an acceleration is susceptibility of drive bunches to beam breakup (BBU) instability [1]. With the purpose to suppress this instability recently it has been proposed to fill the drift channel of dielectric structure with plasma of certain density [2]. The investigations of plasma DWA (PDWA) [2] were made for dielectric wakefield structures with homogeneous radial plasma density. Such consideration is right if pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Note that the case a) corresponds to the absence of plasma in the drift channel, and the case d) -to the complete plasma filling of the said region. From now on the data shown for the case d) have been partially presented in our paper [37]. It can be seen that the cases b) to d) encourage one to choose the position of the accelerated bunch such as to accelerate and focus the bunch simultaneously.…”
Section: Jinst 15 C09001 3 Results Of 25-dimensional Pic-simulationmentioning
confidence: 86%
See 1 more Smart Citation
“…Note that the case a) corresponds to the absence of plasma in the drift channel, and the case d) -to the complete plasma filling of the said region. From now on the data shown for the case d) have been partially presented in our paper [37]. It can be seen that the cases b) to d) encourage one to choose the position of the accelerated bunch such as to accelerate and focus the bunch simultaneously.…”
Section: Jinst 15 C09001 3 Results Of 25-dimensional Pic-simulationmentioning
confidence: 86%
“…[35], which can be described by the parabolic relation for a considerable part of the channel section [36]. The PIC simulation of the test electron bunch acceleration with the model plasma-density dependences [35,36] has shown that the capillary discharge plasma improves the focusing of accelerated bunches [37] in comparison with the case of the uniform plasma density in the section.…”
Section: Jinst 15 C09001mentioning
confidence: 99%
“…The parameters of the structure and bunches, used in the simulations are specified in Table . The p nr for two cases: the plasma fills completely the interior of the dielectric tube (dash lines) and the plasma cylinder of internal radius p1 r = 0.2 mm (solid lines). Red line (2) corresponds to the inhomogeneous distribution of plasma density [15], cyan line (1) is for the homogeneous one…”
Section: The Problem Definitionmentioning
confidence: 99%
“…We have analyzed this possibility analytically and numerically for the case of filling the bunch transport channel of DWA with plasma homogeneous in the cross section [26]. If the plasma is created by means of a capillary discharge [27,28], then the transport of witness electron bunches can even be improved [29,30]. To obtain strong focusing fields, a superdense plasma is not required [30].…”
Section: Introductionmentioning
confidence: 99%